Maternal Near-misses at a Provincial Hospital in Papua New Guinea: A Prospective Observational Study. Issue 3 (September 2018) - Bolnga, J.W.; Morris, M.; Totona, C.; Laman, M.
Abstract : ( Aust N Z J Obstet Gynaecol 2017;57:624–629) Life-threatening pregnancy-related adverse outcomes and maternal deaths are high in developing countries due to health care systems that are weak and resources that are limited. As laboratory facilities with the capacity to undertake postmortem examinations in order to determine causes of maternal deaths are limited in less developed countries, maternal near-miss cases are increasingly being used as a proxy with the goal of understanding factors associated with maternal mortality as well as morbidity. Even within a developing country, the maternal mortality ratio (MMR) tends to be significantly higher in rural areas than urban areas as there is better access to health care facilities in the urban regions. This prospective observational study aimed to determine the near-miss ratio and MMR as well as understand the contributing factors of maternal near-misses and mortality in a provincial level hospital in the Madang Province in Papua New Guinea (PNG). The majority of women living in this province are underprivileged and reside in rural areas.